Removal of Heavy Metal Ions from Aqueous Solution by Alkaline Filtration - Xu, Zitong (Université d'Ottawa / University of Ottawa, 2020)
An innovative approach for the removal of heavy metal ions such as Pb2+ and Cd2+ from aqueous solution was evaluated. It was established that alkaline filtration, which is in essence the combination of alkaline precipitation and membrane filtration, could drastically increase both the efficiency and completeness of Pb2+ or Cd2+ ions removal, producing water whose metal concentration satisfying drinking water standard from a simulation wastewater containing 5 ppm or more Pb2+ or Cd2+ ions. Filtration with three different membranes, including microfiltration (MF), ultrafiltration (UF), and nanofiltration (NF) membranes, were studied at three different pH levels, i.e., 7.0, 8.5, and 10, in terms of metal ion rejection, flux, and permeate pH and at varied dissolved inorganic carbon (DIC) concentration. Increasing the pH of the feed in the tested range would lead to the decrease of metal ion concentration in permeate while flux was in general unaffected. When the feed pH was 10, the Pb2+ concentration in permeate was below 10 ppb regardless of the DIC concentration and membrane for filtration. The effects of DIC concentration were significant but complex. It was found that MF, UF, NF could all effectively reject Pb2+ ions at pH 8.5 and pH 10 although only NF was charged. A hypothesis was proposed to explain the mechanism of alkaline filtration based on experimental data.
Keywords: Membrane filtration; Alkaline precipitation; Lead; Cadmium